The Thermal Emission Spectrum of the Nearby Rocky Exoplanet LTT 1445A b from JWST MIRI/LRS - Patcharapol Wachiraphan; Zachory K. Berta-Thompson; Hannah Diamond-Lowe; Jennifer G. Winters; Catriona Murray; Michael Zhang; Qiao Xue; Caroline V. Morley; Marialis Rosario-Franco; Girish M. Duvvuri (The Astronomical Journal)
The nearby transiting rocky exoplanet LTT 1445A b presents an ideal target for studying atmospheric retention in terrestrial planets orbiting M dwarfs. It is cooler than many rocky exoplanets yet tested for atmospheres, receiving a bolometric instellation similar to Mercury’s. Previous transmission spectroscopy ruled out a light H/He-dominated atmosphere but could not distinguish between a bare-rock, a high-MMW, nor a cloudy atmosphere. We present new secondary eclipse observations using JWST’s MIRI/LRS, covering the 5–12 μ m range. From these observations, we detect a broadband secondary eclipse depth of 41 ± 9 ppm and measure a mid-eclipse timing consistent with a circular orbit (at 1.7 σ ). From its emission spectrum, the planet’s dayside brightness temperature is constrained to 525 ± 15 K, yielding a temperature ratio relative to the maximum average dayside temperature from instant thermal reradiation by a rocky surface R = ${T}_{{\rm{day,obs}}}/T_{{\rm{\max }}}$ = 0.952 ± 0.057, consistent with emission from a dark rocky surface. From an energy balance perspective, such a warm dayside temperature disfavors thick atmospheres, excluding ∼100 bar atmospheres with Bond albedo >0.08 at the 3 σ level. Furthermore, forward modeling of atmospheric emission spectra disfavor simple 100% CO _2 atmospheres with surface pressures of 1, 10, and 100 bar at 4.2 σ , 6.6 σ , and 6.8 σ confidence, respectively. These results suggest that LTT 1445A b lacks a very thick CO _2 atmosphere, possibly due to atmospheric erosion driven by stellar activity. However, the presence of a moderately thin atmosphere (similar to those on Mars, Titan, or Earth) remains uncertain.